Marcadores de estresse oxidativo da saliva de cães com doença periodontal - Silva, Mirtes Rosa da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Periodontal disease (PD) is the most common disease of the oral cavity in dogs with an inflammatory character disease, chronic and infectious. With an excessive production of reactive oxygen species, oxidative stress occurs which is an imbalance between oxidants and antioxidants. Human saliva is considered the first line of defense against oxidative stress in periodontal diseases. Due to lack of studies in dogs on this issue, this study hypotheses were investigated that the similarity to what is described in humans, the DP in dogs cause systemic oxidative stress associated with activation of neutrophils and that saliva can be used to assess this oxidative stress. We selected 20 adult dogs of different breeds and sex, grouped according to the degree of injury (n-6 gingivitis, periodontitis light n-8 and advanced n-6). The control group was made up of the same 20 dogs, 30 days after periodontal treatment, all without any changes on physical examination, serum chemistry profile and complete blood count. To assess oxidative metabolism of circulating neutrophils was measured superoxide production by cytochemical test nitroblue tetrazolium reduction (NBT), and total oxidant concentration (TOC). The concentration of the tiobartbitúrico reactive species (TBARS) in plasma was used to estimate the lipid peroxidation. The local oxidative stress was evaluated by quantifying the TOC and concentration of the main antioxidant in saliva (uric acid, albumin and bilirubin). The systemic oxidative stress in PD has occurred regardless of the degree of injury and is characterized by TOC increase, NBT and TBARS. Changes in oxidative stress biomarkers measured in saliva were not significant and did not show correlation with the values obtained in plasma. Contrary to our hypothesis, the dog saliva analysis does not clearly expressed oxidative stress caused by PD
Keywords: Cães; Doenças periodontais; Antioxidantes; Saliva; Agentes oxidantes; Periodontite; Inflamação; Neutrófilos; Periodontitis